2019
DOI: 10.3390/antibiotics8040254
|View full text |Cite
|
Sign up to set email alerts
|

The Urgent Need for Novel Antimicrobial Agents and Strategies to Fight Antibiotic Resistance

Abstract: Antibiotic resistance in bacterial pathogens has currently reached very high and alarming levels [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
(15 reference statements)
0
19
0
Order By: Relevance
“…The overuse, abuse and misuse of antibiotics in humans and animals have accelerated the development and spread of resistances. It has been suggested that the current "antibiotic resistance crisis" may lead us back to a "pre-antibiotic era" if effective actions to significantly decrease antibiotic use are not undertaken rapidly (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…The overuse, abuse and misuse of antibiotics in humans and animals have accelerated the development and spread of resistances. It has been suggested that the current "antibiotic resistance crisis" may lead us back to a "pre-antibiotic era" if effective actions to significantly decrease antibiotic use are not undertaken rapidly (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…The global spread of antimicrobial resistant bacteria and the emerging consumer trend for natural food preservatives, emphasize the need of exploring novel and natural antimicrobial compounds (Santos-Sanchez et al, 2017;D'Andrea et al, 2019). In this context, microbial diversity in many environments has been a great interest to explore new antimicrobials (Mullis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In previous hydrogenation conditions, the carbonyl groups at the C-ring were also reduced, which had to be recovered by the DDQ oxidation. 19,20d In addition to the synthesis of (1), removal of the benzyl protecting groups of 17 with BBr 3 furnished the B-ring unsaturated core analogue (2).…”
Section: Resultsmentioning
confidence: 99%